Effectiveness of Dual Antiplatelet Therapy (DAPT) to Reduce Stroke Recurrence in Patients with Minor Stroke or High Risk Transient Ischemic Attach (TIA): A Comprehensive Systematic Review - Jeremy Jovanie Owen Tobing; Eka Pranata (International Medical Journal Corp. Ltd, 2025)
Background Patients who experience a minor stroke or a high-risk transient ischemic attack (TIA) are at an increased risk of stroke recurrence. Effective secondary prevention strategies are critical to reducing the burden of stroke-related morbidity and mortality. This systematic review aims to evaluate the effectiveness of DAPT in reducing stroke recurrence in patients with minor stroke or high-risk TIA. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 1.800 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: DAPT is a superior strategy compared to SAPT in reducing stroke recurrence in patients with minor stroke or high-risk TIA. However, its safety concerns, particularly regarding major bleeding, necessitate careful patient selection and treatment duration optimization. Current data suggest that a 21-day DAPT regimen followed by SAPT offers the best balance of efficacy and safety, particularly in patients with atherosclerotic stroke. Future studies should continue refining treatment approaches to maximize the benefits of DAPT while minimizing risks.